ANALISIS KINERJA KEUANGAN DENGAN METODE ALTMAN Z-SCORE PADA PT ACE HARDWARE INDONESIA Tbk - Suteja, I Gede Novian (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2018)
This research purpose is to determine the development of business at PT. Ace Hardware Indonesia, Tbk by looking at secondary data in the form of financial statements from 2011 to 2015. The technique that used in this research is using the method of Altman Z-Score where if the value of Z more than 2,99 is classified as a healthy company. If the value of Z less than 1,81 is classified as a unhealthy company. If the value of Z between 1,81 to 2,99 is classified as a company in the gray area or vulnerable area. From the results of research that has been conducted from 2011 to 2015 based on the financial statements note that PT. Ace Hardware Indonesia, Tbk always has value of Z more than 2,99 which means that the company is not experiencing financial difficulties or in other words the company can be classified as a healthy company.